PENGARUH PEMBELAJARAN DEEP LEARNING TERHADAP HASIL BELAJAR PADA MATA PELAJARAN IPA KELAS VII SMP ISLAM TERPADU KHAIRUL IMAM - Heri Syahputra Azhar Panjaitan; Muhammad Amin Fauzi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study investigates the effect of deep learning instruction on students’ science achievement in Grade VII at SMP Islam Terpadu Khairul Imam, Medan. The research was motivated by the tendency of science learning to remain focused on memorization and teacher-centered activities, which often results in shallow conceptual understanding. The aim of the study is to determine whether deep learning–oriented instruction can significantly improve students’ learning outcomes in science compared to conventional teaching. The research employed a quasi-experimental design with a pretest–posttest control group. The population consisted of two intact classes (N = 36), each comprising 18 students, all of whom were involved as the sample. One class was assigned as the experimental group, receiving deep learning–based instruction, while the other served as the control group with conventional teaching. Data were collected through a science achievement test administered before and after the intervention. Normality and homogeneity tests confirmed that the data met the assumptions for parametric analysis. Paired sample t-tests showed significant improvement in both groups, with a markedly higher gain in the experimental class. Independent samples t-test further indicated a significant difference in posttest scores between the two groups, favoring the experimental class. These findings suggest that deep learning instruction is effective in enhancing junior high school students’ science achievement and is recommended as an alternative approach for science teaching in similar contexts